NGS Technique for Palindromic Sequencing of DNA Through Effective PST-PCR - Saraswat, Prapti (Journal for Research in Applied Sciences and Biotechnology, 2024)
DNA Sequencing technologies have been in use since 1970 and has diversified to much more effective transformations till the date. Initially due to certain drawbacks like cost, time period and requirement of toxic and radioactive elements for the compilation of the process, it remained unintroduced to research setting for complex data in earlier times. One of a technique named as the Sanger technique had more practical approach for sequencing the desired data of the fragments. But the need of DNA sequencing surged after the commencement of the Human Genome Project (HGP) which was a 13 year long collaboration to sequence human genome for understanding its applicable uses.1 At the current stage, the progress moved towards Next Generation Sequencing (NGS) to sequence the fragments of DNA for a better acknowledgement but somehow this did not reported for a fair outcome for palindromic DNA while sequencing. In this rugged sequencing platforms, Roche’s 454 with emulsion PCR technique amplified the templates through beads which later went through pyrosequencing with DNA Polymerase gave the desired output but had a major drawback of high cost.2 Therefore, this study deals with effective PST – PCR technique for studying palindromic DNA in NGS and how it can be considered to fit in all advantages for the above task.